A Multicenter Phase II RCT to Compare the Effectiveness of EMDR Versus TAU in Patients With a First-Episode Psychosis and Psychological Trauma: A Protocol Design - Valiente-Gómez, Alicia; Pujol, Nuria; Moreno-Alcázar, Ana; Radua, Joaquim; Monteagudo-Gimeno, Eila; Gardoki-Souto, Itxaso; Hogg, Bridget; Álvarez, Maria José; Safont, Gemma; Lupo, Walter; Pérez, Victor; Amann, Benedikt L.; et al. (Frontiers in Psychiatry, 2020)
Background: Patients with a first episode psychosis (FEP) who are admitted for the first time to a psychiatric hospital frequently have experienced prior psychological trauma. Additionally, 40-80% develop posttraumatic stress symptoms, which are summarized as a post-psychotic post-traumatic syndrome (PPS). Eye Movement Desensitization and reprocessing (EMDR) therapy could be an effective psychotherapy to treat a PPS and prior psychological traumas in this population. Objectives: To assess if EMDR therapy leads to 1) a reduction of relapses after intervention 2) an improvement of trauma-related, psychotic and affective symptoms, 3) an improvement of overall functioning, and 4) an improvement in quality of life. Methods: This is a multicenter phase II rater-blinded randomized controlled trial in which 80 FEP patients with a history of psychological trauma will be randomly assigned to EMDR (n=40) or to TAU (n=40). Traumatic events will be measured by the Global Assessment of Posttraumatic Stress Questionnaire, the Cumulative Trauma Screening, the Impact of Event Scale-Revised, the Dissociative Experiences Scale, the Childhood Trauma Scale, the Holmes-Rahe Life Stress Inventory, and the Dissociative Experiences Questionnaire. Clinical symptomatology will be evaluated using Suicide and Drug Consumption module of the International Neuropsychiatric Interview, Structured Clinical Interview for Positive and Negative Syndrome Scale, Young's Scale for Mania Evaluation, and Beck Depression II Questionnaire. Functionality will be assessed with the Global Assessment of Functioning and the Quality of Life with the Standardized Instrument developed by the EuroQol Group. The cognitive insight and adherence to the treatment will be assessed with the Beck Cognitive Insight Scale and the Drug Attitude Inventory. All variables will be measured at baseline, post-treatment and at 12-month follow-up. Conclusion: This study will provide evidence of whether EMDR therapy is effective in reducing trauma and clinical symptoms, reducing relapses and in improving functionality and quality of life in patients with FEP and history of trauma.